Educative practices and attitudes within the pre-school environment: evaluating the education professionals - Leonardo dos Santos Antunes; Lívia Azeredo Alves Antunes; Marcos Paulo Fonseca Corvino (Sociedade Brasileira de Pesquisa Odontológica, 2008)
School and family together play an important role in the individual development of children. Therefore, this study aimed at evaluating the practices and attitudes towards oral health care of 245 education professionals working in 24 public municipal pre-schools in Niterói, State of Rio de Janeiro, Brazil. The data were obtained from self-questionnaires consisting of both open and closed questions. The methodology was both quantitative and qualitative, and the quantitative analysis was based on frequency (%). Regarding oral health practices, it was observed that the majority of the education professionals emphasized toothbrushing as a vital method of oral hygiene. In addition, 70.7% of the education professionals performed other types of oral hygiene activities with the schoolchildren, and 17.1% did so with the children's families. All the participants of the study considered that education professionals have a key role in promoting healthy oral habits amongst the schoolchildren and they believe that involving the dentist in educative programs is important. It was therefore concluded that the education professionals surveyed have positive practices and attitudes regarding the children's care, and they recognize their role in fostering healthy habits and developing integrated pedagogic oral health programs.